Seductive academic writing - Freeman, Danyal (Cambridge Scholars Publishing, 2018)
"This volume teaches academics and graduate students how to write seductive academic prose by learning a literacy rarely taught in academic writing or style handbooks: to use literary devices and figures of speech to meet ideals of stylish communication; and how these ideals and supposed 'literary' techniques serve academic readers and writers. Part one explores the persistent problem of the bad academic writing style called 'academese' and argues stylish academic writers avoid it by writing with figures of speech. Part two teaches and illustrates figures of speech seductive writers write into academic prose to convey the music and rhythms of good speech, cohesion, coherence and storytelling, and the personality and passions of the author. Part three argues the academy will not heal itself of academese until academic writing pedagogies teach students to care enough for their readers to write with figures of speech that craft seductive academic writing."--Publisher's website.